PENGARUH KONSENTRASI ROOTONE-F TERHADAP PERTUMBUHAN STEK BAMBU KUNING (Bambusa vulgaris Schrad) - Adewiyah, Rabiatul; Umar, Husain; Muslimin, Muslimin (Universitas Tadulako, 2017)
Cultivation of yellow bamboo still less done IN Palu city. So that , yellow bambu needed to be cultivated. One of the ways to cultivate yellow bamboo is steak. The root growth of yellow bamboo steak (Bambusa vulgaris Schrad) can be stimulated by using Rootone-F substance of growing regulator. The aimed of the research was to find out the effect of Rootone-F to the growth of yellow bamboo steak (Bambusa vulgaris Schrad). The research was conducted on February up to the month of April 2015, that was located in seedbed of Labuan Toposo village Labuan subdistrict. The Research Method applied was Completely Randomdized Design (CRD) which consisted of four treatments M0 = (no treatment), M1= Rootone-F 100ppm, M2 = Rootone-F 200ppm, M3 = Rootone-F 300ppm. Each treatment repeated six times that all needed 24 unit experiments. The variant analysis was done to find out the treatment that tangible and intangible effected, the smallest real difference tes would be done on level 5% if it was tengible. The result of the research showed that Rootone-F substance of growing regulator treatment had tengible effect to accretion of shoots high, number of leaves, stem diameter and root length While intangible affected shoots accretion. The growth was l3sheets, stem diameter was 0,10 mm, number of shoots was 1,33and root lenght was 28,41 cm, then followed by M2 with shoots high everage was 58,03 cm, leaves number was 12,50 sheets, diameter was 0,11 mm, shoot number was 1,17 and root length was 14,35 cm. M3 treatment with 57,03 cm tall, leaves number 11,17 sheets, stem diameter 0,07 mm, bud numbers 1,00 and root length 17,65 cm, moreover the lowest one was on M0 with shoots tall 16,37 cm,leaves number was 4,83 sheets, stem diameter was 0,06 mm, shoots 1,00 and root length was 7,28 cm.Keywords :Bambusa vulgaris Schrad, Rootone-F